On the Methodological Issue of Uncritical Adoption of Concepts Using the Example of the Concept of “Social Distancе” During the COVID-19 Pandemic - Šuvaković, Uroš V. (Sociološki pregled, 2020)
The paper considers the use of the term “social distance” during the COVID-19 pandemic. It is indicated that the term has been uncritically adopted by the scientific medical-epidemiological and public discourse from sociology, and that its subject and content of the concept are essentially different. An argument is proposed for the thesis that such situation was caused, on one hand, by the failure to apply the concretely dialecticallogical rules of definition and, on the other hand, due to ideological attitudes about individualism which are common both to neoliberalism and neoconservatism. The article emphasizes the need to replace the concept of “social distance” in epidemiology with the concept of “physical distance” or just “distance” or “space”.
Keywords: concept (subject, content of the concept); errors of opinion; social distance; physical distance; COVID-19 pandemic; neoliberalism; neoconservatism